Characterizing Minimum-Risk Diet at the Country Level. (29th May 2020) - Lescinsky, Haley; Hayoon, Anna Gershberg; Assmus, Michael; Ferrara, Giannina; Mullany, Erin; Smith, Amanda; Vollset, Stein Emil; Afshin, Ashkan
Abstract: Objectives: Poor diet is a major contributor to the burden of disease globally. However, whether or not sufficient supply of food is available to achieve a minimum-risk diet (MRD) in each country has not been systematically evaluated. Additionally, the future health effects of adopting a MRD have not yet been quantified. To address these gaps in knowledge, we estimated the gaps between current and optimal consumption and availability of major food groups in 196 countries. We also estimated the number of deaths that would be saved in 2050 if the world population adopted MRD by 2030. Methods: Using the data and methods of the Global Burden of Disease (GBD), we estimated the energy intake required to maintain a healthy active life in each country by age and sex. Then, we defined the country-specific MRD as the diet that provides the required energy through sufficient intake of healthy foods, minimal intake of unhealthy foods, and balanced intake of diverse neutral foods that are available in the country. Using the GBD Diet Database, we then assessed the gap between consumption and availability of each food group by comparing its current intake and availability with the intake and availability required to achieve MRD. Finally, we used Institute for Health Metrics and Evaluation forecasting methodology to evaluate the disease burden under a reference and two alternate scenarios (i.e., adopting MRD, adopting MRD and stabilizing BMI). Results: We found a significant gap in the availability of healthy foods globally, with the largest gaps in nuts (60% of optimal availability), fruits (70%), and vegetables (80%). Our forecasting analyses show that 2.3 million deaths (38 deaths per 100, 000 population) can be prevented in 2050 if the world adopts the MRD by 2030. Across geographic regions, the largest number of deaths prevented will be in Oceania (121 deaths per 100, 000 population) and Central Asia (85 deaths per 100, 000 population). In addition to achieving MRD, stabilizing the future trend in BMI would result in 4.6 million deaths globally (60 deaths per 100, 000 population) averted in 2050. Conclusions: Our results inform national policies aiming at improving diet and highlight the need for a radical transformation in the food system to increase the production, distribution, and availability of healthy components of diet. Funding Sources: The Rockefeller Foundation, Bill and Melinda Gates Foundation.